Effect of supercritical CO2 on the copolymerization behavior of cyclohexene oxide/CO2 and copolymer properties with DMC/salen-Co(III) catalyst system - Meng, Qing-Yang; Pepper, Katie; Cheng, Rui-Hua; Howdle, Steven M.; Liu, Bo-Ping (Wiley, 2016)
The copolymerization of cyclohexene oxide (CHO) and carbon dioxide (CO2) was carried out under supercritical CO2 (scCO2) conditions to afford poly (cyclohexene carbonate)(PCHC) in high yield. The scCO2 provided not only the C1 feedstock but also proved to be a very efficient solvent and processing aid for this copolymerization system. Double metal cyanide (DMC) and salen-Co(III) catalysts were employed, demonstrating excellent CO2/CHO copolymerization with high yield and high selectivity. Surprisingly, our use of scCO2 was found to significantly enhance the copolymerization efficiency and the quality of the final polymer product. Thermally stable and high molecular weight (MW) copolymers were successfully obtained. Optimization led to excellent catalyst yield (656 wt/wt, polymer/catalyst) and selectivity (over 96% toward polycarbonate) that were significantly beyond what could be achieved in conventional solvents. Moreover, detailed thermal analyses demonstrated that the PCHC copolymer produced in scCO2 exhibited higher glass transition temperatures (Tg ~114 8C) compared to polymer formed in dense phase CO2 (Tg~77 8C), and hence good thermal stability. Additionally, residual catalyst could be removed from the final polymer using scCO2, pointing toward a green method that avoids the use of conventional volatile organic based solvents for both synthesis and work-up.